Venture Capital Backing and Issuance of Seasoned Equity Offerings: Evidence from China. (11th December 2020) - Yang, Songling; Li, Hemei; Li, Juncheng; Zhang, Qiuyue; Shi, Qianqian
Abstract: We analyze how venture capital (VC) affects the timing of seasoned equity offering (SEO) issuance and the post‐SEO performance of Chinese companies during the 2006–2018 period. Empirical analysis confirms that VC "accelerates" SEO issuance because of greater financing demands. Thus, VC‐backed firms prefer to issue their first SEOs earlier than non‐VC‐backed firms. Moreover, quick SEOs promoted by venture capitalists are more underpriced because of information asymmetry.